MANIA IN TWINS : A CASE REPORT - Srivastava, Shrikant (Medknow Publications, 1996)
A 19 year old patient presented with a first episode of mania. A year ago his twin brother had developed a similar illness. In the family, there was no other history of psychiatric disorders.